2018
DOI: 10.1088/1741-4326/aad059
|View full text |Cite
|
Sign up to set email alerts
|

Two-plasmon decay instability of the backscattered light of stimulated Raman scattering

Abstract: The two-plasmon decay (TPD) instability of the backscattered light of the simulated Raman scattering (SRS) is first investigated with the help of one-dimensional (1D) and two-dimensional (2D) particle-in-cell (PIC) simulations. The 2D PIC simulation results show that the backscattered light of the SRS does excite TPD instability. Further, the comparison between 1D and 2D PIC simulation results shows that the backward SRS is suppressed by the excitation of TPD instability, which means the TPD instability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A two dimension (2D) particle-in-cell (PIC) code EPOCH 49,50 is used to research SRS and SBS of BSRS. The electron temperature is = .…”
Section: Methodsmentioning
confidence: 99%
“…A two dimension (2D) particle-in-cell (PIC) code EPOCH 49,50 is used to research SRS and SBS of BSRS. The electron temperature is = .…”
Section: Methodsmentioning
confidence: 99%
“…However, many nonlinear processes are still unclear in ICF experiments. In indirect-drive ICF conditions, electrons generated by SRS are usually below 100 keV, but both re-scattering [ 21 ] and TPD of the scattered light of SRS [ 22 ] may generate super-hot electrons with energy that exceeds 100 keV, which were detected in ICF experiments [ 23 ] . However, these secondary processes caused by nonlinearities are usually ignored or attract less attention because they are difficult to detect in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, with the help of 2D particle-in-cell (PIC) simulations [ 24 ] , we discuss the competition among three instabilities, namely two secondary instabilities, which are the TPD of the backscattered light and filamentation of the EPWs, and a primary instability, which is the SSRS of the laser. As discussed in our previous work [ 22 ] , the TPD of the backscattered light will be excited in a plasma with an electron density near (where cm is the critical density of the laser and is the laser wavelength in unit μm) and this secondary instability will suppress BSRS and generate super-hot electrons with energy exceeding 100 keV. Here it is further found that this secondary instability will compete with another two instabilities, one of which is filamentation of the EPWs and the other is SSRS of the laser.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms that have been studied to date. include SRS rescatterings, corresponding Langmuir decay instability (LDI) [9,10] and the two-plasmon decay instability [11,12]. Other authors [13][14][15][16] have investigated the electrons accelerated by the forward-SRS-induced Langmuir waves.…”
Section: Introductionmentioning
confidence: 99%